Evaluation of Quality of Chia (Salvia hispanica), Sesame (Sesamum indicum), and Quinoa (Chenopodium quinoa) Oils - Maria Paula Fortuna Clara (Brazilian Archives of Biology and Technology)
Abstract Each year, the consumption of vegetable oils increases gradually. Some oils, such as chia, sesame, and quinoa, are consumed due to the nutritional properties and health promoters that have been recognized in their components. Based on this premise, the present study aimed to characterize chia (Salvia hispanica), sesame (Sesamum inducum), and quinoa (Chenopodium quinoa) oils, in order to enable their applications in the development of new food products. Chia oil presented higher degradation, as it stood out with higher amounts of free fatty acids (4.46%) and peroxide value (18.35 meq/kg). It is an oil that is rich in polyunsaturated fatty acids (75.47%), and, consequently, with high refractive index (1,475) and iodine value (192.86 g/100 g). Quinoa oil stood out for its higher oxidative stability (17.55 h) and higher amount of phenolic compounds (190.84 mg/100 g). Sesame and quinoa oils showed no significant difference for carotenoids, but sesame oil had higher content of total tocopherols (656.50 mg/kg). Thus, the oils can be used in technological processes and/ or in the formulation of new food products, in order to their increase the nutritional value.